Multi-character taxonomic review, systematics, and biogeography of the Black-capped/Tawny-bellied Screech Owl (Megascops atricapilla-M. watsonii) complex (Aves: Strigidae) - Dantas, Sidnei M.; Weckstein, Jason D.; Bates, John; Oliveira, Joiciane N.; Catanach, Therese A.; Aleixo, Alexandre (Zootaxa, 2021)
Megascops is the most species-rich owl genus in the New World, with 21 species currently recognized. Phylogenetic relationships within this genus are notoriously difficult to establish due to the considerable plumage similarity among species and polymorphism within species. Previous studies have suggested that the widespread lowland Amazonian M. watsonii might include more than one species, and that the Atlantic Forest endemic M. atricapilla is closely related to the M. watsonii complex, but these relationships are as yet poorly understood. A recently published phylogeny of Megascops demonstrated that M. watsonii is paraphyletic with respect to M. atricapilla and that genetic divergences among some populations of M. watsonii are equal to or surpass the degree of differentiation between some M. watsonii and M. atricapilla. To shed light on the taxonomic status of these species and populations within them, we conducted a multi-character study based on molecular, morphological, and vocal characters. We sequenced three mitochondrial (cytb, CO1 and ND2) and three nuclear genes (BF5, CHD and MUSK) for 49 specimens, covering most of the geographic ranges of M. watsonii and M. atricapilla, and used these sequences to estimate phylogenies under alternative Bayesian, Maximum Likelihood, and multilocus coalescent species tree approaches. We studied 252 specimens and vocal parameters from 83 recordings belonging to 65 individuals, distributed throughout the ranges of M. watsonii and M. atricapilla. We used Discriminant Function Analysis (DFA) to analyze both morphometric and vocal data, and a pairwise diagnostic test to evaluate the significance of vocal differences between distinct genetic lineages. Phylogenetic analyses consistently recovered six statistically well-supported clades whose relationships are not entirely in agreement with currently recognized species limits in M. watsonii and M. atricapilla. Morphometric analyses did not detect significant differences among clades. High plumage variation among individuals within clades was usually associated with the presence of two or more color morphs. By contrast, vocal analyses detected significant differentiation among some clades but considerable overlap among others, with some lineages (particularly the most widespread one) exhibiting significant regional variation. The combined results allow for a redefinition of species limits in both M. watsonii and M. atricapilla, with the recognition of four additional species, two of which we describe here as new. We estimated most cladogenesis in the Megascops atricapilla-M. watsonii complex as having taken place during the Plio-Pleistocene, with the development of the modern Amazonian and São Francisco drainages and the expansion and retraction of forest biomes during interglacial and glacial periods as likely events accounting for this relatively recent burst of diversification.